Lay counselors experiences with counseling their peers; the impact of being a lay counselor and providing therapy to traumatized Sudanese refugees in Cairo - Ibrahim, Baher (AUC Knowledge Fountain, 2015)
This research is a qualitative study into how lay counselors are affected by their training in and practice of a community-based lay counseling intervention. A group of refugees from a Sudanese refugee community in Cairo, Egypt were trained in Narrative Exposure Therapy and subsequently provided it to members of their community suffering from post-traumatic stress disorder (PTSD). Narrative exposure therapy (NET) is a short-term psychotherapy based on the principles of cognitive behavioral therapy (CBT), exposure therapy and testimony psychotherapy. NET has been shown to be effective in relieving symptoms of PTSD in refugees. After completing the training and completing NET with one client, semi-structured interviews with the trained lay counselors were conducted to discover the impact of the training and provision of therapy to their peers on them. Background literature suggests that serving as a lay counselors may have one of two effects; the lay counselors may become psychologically empowered from the experience of helping their peers (Alexander, Mollink & Seabl, 2010), or they may suffer from the effects of secondary stress syndrome as a result of exposure to the traumatic memories of their peers (Peltzer, Matseke & Louw, 2014; Shah, Garland & Katz, 2007). Thematic analysis of interviews conducted with the lay counselors revealed that the experience of training and providing therapy was a largely positive one from which they emerged psychologically empowered and motivated. In addition, several other themes were identified. These include the suffering of Sudanese refugees, a strong sense of community, resilience and coping strategies and logistic challenges and cultural barriers to providing therapy in the community. Implications for future research as well as future community based lay counseling mental health interventions in the Sudanese refugee community in Cairo are discussed.